Evaluation of professional responsibility of civil servants - Abdykalikova, M. N.; Berdibayeva, S. K. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2018)
Responsibility is one of the personal qualities that manifests itself in the process of the activity of a civil servant. The article is devoted to the study of the locus of control: the internal and external locus of control of a modern civil servant. The method used to measure the level of the G. Rotter’s locus of control, in which there are such scales or needs of six categories as: recognition status, protection-dependence, domination, indepen-dence, love and affection, physical comfort. It was assumed that since effective civil servants are primar-ily responsible employees, they will be characterized by internality, and ineffective – externality. The external structure of professional responsibility is represented by the subject object and authority. In this case, the subject is a specialist, the object is his professional activity, and the instance is the professional branch, the public service. The internal structure consists of cognitive, motivational, emotional-volitional and behavioral elements. The cognitive element represents knowledge of the essence of professional accountability, as well as social, moral and legal norms of behavior, conviction. Thus, professional responsibility is the integral quality of a specialist, which manifests itself in the ability to make informed decisions in the sphere of his professional activity, to show perseverance and conscientiousness in their implementation and in readiness to be accountable for their results and con-sequences. Key words: professional responsibility, internality, externality, installation, social responsibility.